The peaceable kingdom : a primer in Christian ethics - Hauerwas, Stanley, 1940- (University of Notre Dame Press, 1983)
Examines Christian ethics in a fragmented and violent world. Considers historical perspectives and the task of ethics. Focuses on the peaceable kingdom, the servant community, and the spirituality of peaceableness.